Experimental investigation of the meteorologically influenced sound propagation through an inhomogeneous forest site - Astrid Ziemann; Manuela Barth; Markus Hehn (Meteorologische Zeitschrift, 2013)
The low-frequency sound propagation was investigated at a clearing and an adjacent forest stand at the meteorological Anchor Station Tharandter Wald near Dresden (Germany) using measurements and simple models. Thereby, the sound propagation is dependent on the distance to the sound source as well as on the acoustic properties of the ground surface and the canopy. Particular attention was paid to the meteorological influence on the sound propagation because the modified meteorological regime in forest areas leads to a changed sound propagation in comparison to the unaffected case. The measurements were carried out in the late summer time of 2011. The propagation of acoustic signals was recorded along a sound path of 115 m at a clearing and 75 m in an old spruce stand. Besides the acoustic measurements the atmospheric state was investigated using a micro-meteorological mast of a height of 40 m. First results demonstrate a noticeably meteorological influence on sound propagation even at short distances of some 10 m.